Role of arbuscular mycorrhizal fungus Rhizophagus custos in the dissipation of PAHs under root-organ culture conditions - Aranda, Elisabet (2013)
Polycyclic aromatic hydrocarbons (PAHs) are one of the most common contaminants in soil. Arbuscular mycorrhizal (AM) fungi make host plants resistant to pollutants. This study aims to evaluate the impact of anthracene, phenanthrene and dibenzothiophene on the AM fungus Rhizophagus custos, isolated from soil contaminated by heavy metals and PAHs, under monoxenic conditions. We found a high level of tolerance in R. custos to the presence of PAHs, especially in the case of anthracene, in which no negative effect on AM-colonized root dry weight (root yield) was observed, and also a decrease in the formation of anthraquinone was detected. Increased PAH dissipation in the mycorrhizal root culture medium was observed; however, dissipation was affected by the level of concentration and the specific PAH, which lead us to a better understanding of the possible contribution of AM fungi, and in particular R. custos, to pollutant removal.